A multimodal analysis of the representations of gender in contemporary South African children's picture books produced by Book Dash - Heydenrych, Ellen Frances (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2020)
In response to a demand for quality children's picture books written and published by South Africans for local children, Book Dash "“ a South African non-profit organisation "“ has devised a publishing model in which they produce high quality children's picture books in a twelve-hour period. Their aim is to publish books that represent a diverse range of South African children. However, while their objective is to create books that are representative of many races, this representation happens through gendered characters. In this thesis, I explore the representation of gender in Book Dash's picture books. I use a combination of visual social semiotics, narrative theory, and critical discourse analysis, specifically focusing on the gendered ways in which the characters are represented. My analysis of these books shows how complex it can be to contest regimes of representation that work to fix patriarchal discourses and gender inequality. My findings reveal a paradox in the representation of gender norms in female characters, as some girl child characters are represented in roles that challenge gender norms, while female adult characters are consistently represented as conforming to the patriarchal feminine ideal. There is also a notable lack of father figures in these books. Such portrayals may contribute to the perpetuation of patriarchal discourses and gender inequality, particularly if these books are held up as examples of equality.
Keywords: Book Dash (South Africa); Picture books for children -- South Africa; Sex role in literature; Patriarchy in literature; Children's literature, -- South African (English) -- 21st century -- History and criticism